Islam and HIV related social services in Malaysia. Issue 1 (3rd April 2017) - Shaw, Stacey A.; Saifi, Rumana; Lim, Sin How; Saifuddeen, Shaikh M.; Kamarulzaman, Adeeba
ABSTRACT: We review HIV prevention and treatment efforts involving Islam in Malaysia. The Department of Islamic Development Malaysia (JAKIM) conducts HIV-related workshops with Muslim leaders and lesbian, gay, bisexual, and transgender (LGBT) communities. A methadone maintenance treatment (MMT) project was implemented in a mosque in Kuala Lumpur, incorporating religious and social supports alongside provision of health services. Additional services including premarital HIV testing are discussed. Islamic values point to the need for compassion, nonjudgment, and taking action to improve lives, while reluctance to support harm-reduction strategies among sexual minorities highlights the important role of community advocates and social workers within nongovernmental organizations.